Preparing for coastal change - Zong, Yongqiang (2013)
Coastal areas are dynamic environments that are home to billions of people worldwide and provide areas of unique natural importance. As such, coastal change is of considerable local and global interest, not only within the geological realm, but also in terms of socioeconomic and biodiversity impacts. An accurate understanding of how changes in relative sea level, geological processes and extreme events, such as storms and tsunamis, have interacted to shape and change the Earth's coastlines over millennia is fundamental to future projections of coastal change. On the basis of this, researchers in these, and various other aspects of coastal change were brought together in late 2010 at the University of Hong Kong for the first meeting of International Geoscience Program Project 588 (IGCP588) – Preparing for Coastal Change. This special issue showcases some of the results presented at this meeting.